Do Consumers Want Seaweed in Their Food? A Study Evaluating Emotional Responses to Foods Containing Seaweed - Rachael Moss (MDPI AG, 2021)
Seaweeds are nutrient-dense marine organisms that have been proposed as a key ingredient to produce new functional foods. This study’s first objective was to identify consumers’ emotional responses and purchase intent towards a variety of food products containing seaweed. The secondary objective was to evaluate how hunger status and lifestyle affect consumers’ emotional responses. Participants (n = 108) were asked to evaluate pictures of different food items containing seaweed (beef burger, cheddar cheese, fettuccine, fish filet, sausage, bread, yogurt, and dried seaweed) using the CATA variant of EsSense25 Profile® and a purchase-intent scale. The consumers also answered questions about their hunger status, food neophobia, food-related lifestyle, as well as open-ended comment questions about seaweed. Participants’ purchase-intent scores were highest for bread and dried seaweed, which they associated with positive emotions. The participants disliked yogurt and sausage, indicating that they were disgusted with them. Participants believed seaweed could be added to fish, savoury, and cereal grains-based foods. The participants’ hunger status as well as their food neophobia and lifestyle impacted their emotional responses. Future research should continue to investigate how emotions affect purchase intent, how participant’s hunger status affects their emotions, and how participants’ lifestyle changes how they perceive new food products.